How Does Porcine Epidemic Diarrhea Virus Escape Host Innate Immunity? - Jinyuan Li; Hao Lu; Gaowei Hu; Shengmei Pang; Yuqing Xie; Guoqiang Zhu; Xueyan Ding (Pathogens, 2025)
Porcine epidemic diarrhea virus (PEDV), the causative agent of porcine epidemic diarrhea (PED), induces vomiting, watery diarrhea, and severe dehydration in pigs. It exhibits particularly high lethality in neonatal piglets, posing a significant threat to the global swine industry and inflicting substantial economic losses. The host innate immune system serves as the primary defense against viral invasion; however, PEDV employs multiple strategies to evade this response. This review systematically summarizes the multiple molecular mechanisms by which PEDV evaded the host’s innate immunity, including interfering with host intracellular signaling pathways by virally encoded proteins, antagonizing the host’s antiviral factors and related immune genes to suppress the innate immune responses, and regulating the autophagy process of the host cells, thereby achieving the escape of the host’s innate immunity. A comprehensive understanding of how PEDV subverts innate immunity is crucial for developing effective control strategies and therapeutics. This review aims to provide novel insights and potential targets for combating PED.